2023
DOI: 10.1177/11206721231171623
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase expression (DNMT1, DNMT3a and DNMT3b) as a potential biomarker for anti-VEGF diabetic macular edema response

Abstract: Purpose DNA methylation is involved in Diabetic Retinopathy progression showing a metabolic memory mechanism. However, the association of DNA methyltransferase with diabetic macular edema is still unknown. We aimed to describe the differences in DNA methyltransferase gene expression in patients with different diabetic macular edema responses. Methods A total of 27 diabetic patients, aged 59–90 years, were prospectively enrolled in this cross-sectional study. The participants were classified into control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Extensive population studies have consistently reported a significant decline in visual acuity and ERG responses in individuals with PDR, and the presence of neurodegeneration in all phenotypes of DR [ 55 , 56 ]. The shortened and disorganized photoreceptor outer segments contribute to a reduction in a-wave amplitude [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive population studies have consistently reported a significant decline in visual acuity and ERG responses in individuals with PDR, and the presence of neurodegeneration in all phenotypes of DR [ 55 , 56 ]. The shortened and disorganized photoreceptor outer segments contribute to a reduction in a-wave amplitude [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advent of anti-VEGF therapy demonstrated remarkable clinical benefits; however, the majority of patients failed to achieve clinically significant visual improvement, and there are limitations such as some cases lacking response to anti-VEGF therapy and short half-life of drugs requiring repeated injection [ 4 ], so it is urgent to develop new therapeutic methods. According to a recent clinical study on patients with diabetic macular edema, patients who were insensitive to the anti-VEGF response had significantly higher levels of DNMT1 expression than patients who were sensitive to it [ 51 ]. This finding raises the possibility that regulating DNA methylation may be crucial to the complementary treatment of DR.…”
Section: Discussionmentioning
confidence: 99%